Controlling Transmission of MRSA to Humans During Short-Term Visits to Swine Farms Using Dust Masks - Angen, Øystein; Skade, Lotte; Urth, Tinna Ravnholt; Andersson, Mikael; Bækbo, Poul; Larsen, Anders Rhod (Frontiers in Microbiology, 2019)
The aim of the investigation was to determine the protective effect of wearing dust masks to prevent MRSA contamination during a short-term visit in a MRSA-positive swine farm. A total of 118 human volunteers were randomly allocated to a group wearing masks and to the control group. On average, 9% of the participants wearing masks were MRSA-positive when leaving the farm compared to 62% of the participants not wearing masks. At day 1, 2, and 7after the farm visit, none of those wearing masks were MRSA-positive. An odds ratio of 18.9 (CI: 6.4-56.2) for being MRSA-positive was found for those not wearing masks compared to those wearing masks when including the farm as random effect. None of the covariates (gender, age and smoking) influenced the OR for being MRSA-positive when leaving the farm. In addition, 106 volunteers not wearing masks were investigated in order to provide an estimate of a contamination dose of airborne MRSA. Due to the high variation in the MRSA measurements, it was not possible to establish a stable estimate for this. Out of the 106 volunteers not wearing masks, 6%, 7%, and 3% tested MRSA-positive 1, 2, and 7 days after the farm visit, respectively.